Therapeutic ultrasound versus injection of local anesthetic in the treatment of women with chronic pelvic pain secondary to abdominal myofascial syndrome: a randomized clinical trial - Maria Carolina Dalla Vecchia Baltazar; Jéssica Aparecida de Oliveira Russo; Victória De Lucca; Andréia Moreira de Souza Mitidieri; Ana Paula Moreira da Silva; Maria Beatriz Ferreira Gurian; Omero Benedicto Poli-Neto; Júlio César Rosa- (BMC, 2022)
Abstract Background Chronic pelvic pain (CPP) is defined as recurrent or continuous pain in the lower abdomen or pelvis, either non-menstrual or noncyclical, lasting for at least 6 months. There is strong evidence that up to 85% of patients with CPP have serious dysfunctions of the musculoskeletal system, including abdominal myofascial pain syndrome (AMPS). AMPS is characterized by intense and deep abdominal pain, originating from hyperirritable trigger points, usually located within a musculoskeletal band or its lining fascia. In the literature, there are few studies that address AMPS. Objectives To evaluate and compare the efficacy of therapeutic ultrasound (TUS) and injection of local anesthetic (IA) to improve pain in women with abdominal myofascial syndrome secondary to CPP. Study design Randomized controlled clinical trial. Setting Tertiary University Hospital. Materials and methods A randomized clinical trial was conducted, patients were allocated to two types of treatment: group TUS (n = 18), and group IA (n = 20). The instruments used for evaluation and reassessment were the Visual Analog Scale, Numerical Categorical Scale, McGill Pain Questionnaire, and SF-36 quality of life assessment questionnaire. They were evaluated before starting treatment, 1 week after the end of treatment, and at 1, 3, and 6 months. Results TUS and IA were effective in reducing clinical pain and improving quality of life through the variables analyzed among study participants. There was no significant difference between groups. Limitations: absence of blinding; exclusion of women with comorbidities and other causes of CPP, the absence of a placebo group, the difference between the number of sessions used for each technique, and the COVID-19. Conclusion Treatment with TUS and IA were effective in reducing clinical pain and improving quality of life in women with AMPS secondary to CPP. Trail registration We declare that this clinical trial has been registered under the number [(ReBEC) no. RBR-39czsv] on 07/18/2018 in the Brazilian Registry of Clinical Trials.